Efektivitas Penggunaan Media Geoboard Dalam Pembelajaran Joyful Learning Untuk Materi Bangun Datar Di Kelas III SD Muhammadiyah Mimbar - Hamdana Hadaming; Muis, Nur Rahmawati Muis; Sitti Fithriani Saleh (Jurnal Riset Evaluasi Pendidikan, 2024)
The aim of the research is to find out how effective geoboard media is used in joyful learning for flat building material in class III of Muhammadiyah Mimbar Elementary School. The type of research used is pre-experiment with a quantitative research approach. The sampling technique used in this research used a saturated sampling technique. The sample taken from all class III students at SD Muhammadiyah Mimbar was 27 students consisting of 13 men and 14 women. The research design used is One-Group Pretest-Posttest design . The instruments used in this research were learning implementation observation sheets, student activity observation sheets, student response questionnaires, and learning outcomes. The data analysis techniques used in this research are observation data (implementation of learning and student activities), questionnaires, and learning outcomes. The results of descriptive statistics show that the average score for mathematics learning outcomes before using geoboard media in joyful learning is in the very low category, namely 46.8% of the ideal score of 100 with a standard deviation of 17.3. Meanwhile, the average mathematics learning outcomes of students after implementing the use of geoboard media in joyful learning are in the high category, namely 90.1% of the ideal score of 100 with a standard deviation of 10.1. This shows that there are differences in students' mathematics learning outcomes before and after applying geoboard media in joyful learning . The research results show (1) the percentage of learning implementation by teachers is very high at 3.6; (2) the percentage of students who actively participate in the mathematics learning process is 95.36%; (3) the percentage of students who gave positive responses was 78.92% and; (4) the mathematics learning outcomes of students after applying the use of geoboard media in joyful learning are better than the mathematics learning results before applying the use of geoboard media in joyful learning . From the results of this research it can be concluded that mathematics learning is effective through the use of geobard media in joyful learning for class III students at SD Muhammadiyah Mimbar.